UNDANG-UNDANG 16 TAHUN 2019 PERUBAHAN ATAS UNDANG - UNDANG NOMOR. 1 TAHUN 1974 TENTANG PERKAWINAN - Dewi Robiyanti (Berajah Journal, 2026)
The amendment to Law No. 1 of 1974 through Law No. 16 of 2019 equalizes the minimum marriageable age for men and women at 19 years. Observation in Kec. Marindal 1 G. Baru Village aimed to assess the implementation of this rule. The method involved direct observation and informal interviews. Findings reveal some community understanding, but underage marriages still occur. Conclusion: strengthened legal outreach and administrative monitoring are needed to effectively prevent child marriage.